Scientific Attitude Assessment Instruments Using Self-Assessment in Project-Based Learning Development - Fathayati, Siti; Isnaeni, Wiwi; Marianti, Aditya (Journal of Innovative Science Education, 2022)
Scientific attitude is very important in learning activities. In addition, one of the learning objectives stated that students must have character. Students must be able to solve problems scientifically to form a good character or attitude. Such learning can be realized by using contextual learning such as project-based learning, as well as using standard scientific attitude assessment instruments. However, this affective assessment has been less emphasized. Most educators prioritize cognitive aspects in their assessment activities. For this reason, it is necessary to develop a scientific attitude assessment using self & peer assessment in project-based learning. This research is a kind of R&D research that used the ADDIE development model. The purpose of this study is to analyze the validity of the instrument, the practicality of the instrument, and the effectiveness of the developed scientific attitude assessment instrument by using self & peer assessment in project-based learning. The sample used in this study was class VII A and B SMP N 04 Lambu Kibang totaling 48 students. The lesson taught was about environmental pollution. The results of the validity of the instrument analyzed using the CVR obtained 0.9. This means that the instrument validity was good. The results of the instrument's effectiveness can be seen from the scientific attitude that has excellent criteria. The assessment used in this study was only self-assessment because of the limited learning activities due to the COVID-19 pandemic. The first learning step is having a scientific attitude of critical thinking, responsibility, and care for the environment. The second is having curiosity, perseverance, and responsibility. The third is having curiosity, critical thinking, and being objective. In the fourth learning step, the scientific attitudes that have excellent criteria are the attitude of being curious, objective, and persevering. The fifth learning step is being disciplined, caring for the environment, and having a critical thinking attitude. The sixth is an attitude of curiosity, perseverance, and responsibility.